The role of HLA-B27 in the pathogenesis of spondyloarthritis - McHugh, K (2011)
The Human Leukocyte Antigen (HLA)-B27 is a Major Histocompability Complex (MHC) class I antigen that is strongly associated with development of a group of closely related arthritic diseases, collectively known as the spondyloarthropathies (SpA). However, the mechanism by which HLA-B27 confers this susceptibility is unclear. Studies have shown that HLA-B27 heavy chains can form classical heterotrimers associated with peptide and β2-microglobulin (B27HT), and also non-classical heavy chain homodimers (B27₂). B27₂ assemble intracellularly during maturation and are also expressed at the cell surface following endosomal recycling of B27HT. A pathogenic role for B27₂ has been proposed in two of the current theories of pathogenesis: the B27 homodimer theory and the B27 misfolding and UPR theory. Yet, determinations of the extent, distribution, and triggers of B27₂ expression, as well as the functional consequences of its receptor interactions in AS pathogenesis, have been hampered by the lack of a specific detection reagent. Therefore, to investigate the role of B27₂ in AS, we generated a novel antibody to B27₂ – HD6 – using phage display technology, which binds to in vitro refolded B27₂ but not B27HT complexes by ELISA. This thesis provides evidence that HD6-reactive molecules, which include B27₂, are expressed at the cell surface in both cell lines and in the context of a disease setting. Recognition is B27-specific and strongly correlated with the magnitude of B27 expression, which could account for the lack of staining in some cell subsets. Moreover, staining was comparable in cell lines expressing the disease-associated B*27:05 and the less disease-associated subtype B*27:09. In addition, I have shown cells expressing physiologic levels of B27, including EBV-transformed BCLs and AS patient PBMCs, are capable of expressing the HD6 epitope upon low pH treatment. Interestingly, these ‘acid-inducible HD6’ molecules were absent from cells lacking a functional PLC. Finally, I have shown that HD6-reactive molecules can derive from pre-existing folding B27 molecules at the cell surface, which may be inhibited by the addition of exogenous B27-binding peptides. These findings are consistent with a mechanism of pathogenesis involving the surface expression and recognition of B27₂ and/or other aberrantly folded forms of B27, as proposed in the homodimer theory. HD6 will be a powerful tool to address the potential pathogenic role of B27₂ in SpA and may additionally have therapeutic potential.